Evaluation of Community-Based Waste Management TPS 3R "KSM Barat Asri" in West District, Magetan Regency - Tia Monica Kristiana (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
TPS 3R "KSM Barat Asri" has piles of garbage that smells bad and attracts flies, there are residents settlements with a distance of <500 meters which can have the risk of contaminating the water of the residents dug wells. This study aims to evaluate waste management at TPS 3R "KSM Barat Asri". This type of research was descriptive research using a qualitative approach, the research subject was the head of TPS 3R "KSM Barat Asri" and the object of research was waste management at TPS 3R "KSM" Barat Asri. Data collection was carried out by observation, measurement and interviews with the research variables for location requirements, volume, type of waste, transported volume, frequency of waste transportation, human resources, level of density and fly control. The results of this study are that the distance between TPS 3R and settlements does not meet the requirements but the location was easily accessible and not a flood-prone area, the average waste generated is 7,5 m3 per day with a ratio of 33% organic waste and 67% inorganic waste. The residual waste volume that can be transported by the Armroll truck is 6,5 m3 and the transport was carried out every 2 days. Human resources in TPS 3R do not meet the requirements both in quality and quantity. The density of flies in TPS 3R was 27 and belonged to the very high category.Keywords: waste management; waste residue; garbage transport